Effect of shaded colors cage on mating behavior, eggs weight, and adult survival of black soldier fly (Hermetia illucens L.) - Syafrina Lamin,; Arfan Abrar,; Nina Tanzerina,; Rahmat Pratama,; Nurul Fatiha, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The growing economic demand for Black Soldier Fly (BSF) or Hermetia illucens larvae in the animal feed industry surpasses the current low production of BSF eggs. The insufficient production and population of BSF pose a challenge, necessitating the development of technology and strategies for mass rearing of H. illucens. To address this, efforts were made to enhance egg productivity by manipulating mating behavior and egg weight through exposure to different light spectra based on H. illucens photoreceptors. Four plastic cage shaded colors (clear, yellow, red, and blue) to optimize egg production and observing mating behavior were conducted from November 29, 2022 to January 7, 2023, at the Animal Physiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Sriwijaya, Indralaya, Indonesia. The data collected were the number of mating pairs, copulation duration, average egg weight, and the adult lifespan of H. illucens. The shade color was found to significantly influenced mating behavior and egg weight, with the blue shade treatment yielding the best results. Specifically, the blue shade stimulated mating behavior, resulting in the highest number of mating pairs (7.71±1.38) and an mean copulation duration of 33.47±1.56 min. While optimum egg weight increased by 0.25±0.12, and it had no impact on the lifespan of H. illucens from eggs to death